ANALISIS TEMA DAN NILAI-NILAI DIDAKTIS PADA NOVEL KAMI BUKAN SARJANA KERTAS KARYA J.S KHAIREN - Cinthia Claudia Duma Napitupulu; Junifer Siregar; Vita Riahni Saragih (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This thesis aims 1) to describe the themes contained in the novel We're Not Bachelor Papers by J.S Khairen 2) to describe the didactic values ​​contained in the novel We're Not Bachelor Papers by J.S Khairen. This research uses a qualitative descriptive method. Data sources are the novel We're Not Bachelor Ketas by J.S Khairen and books, references, journals and theses. Data collection techniques are reading, listening and note-taking techniques. The data analysis technique uses descriptive analysis techniques. The results of this research show that 1) themes were found that appeared in the novel Kami Bukan Suhu Kertas by J.S Khairen, namely major themes and minor themes. 2) didactic values ​​were found including moral values, social values ​​and religious values ​​that appeared in the novel Kami Bukan Bachelor Paper by J.S Khairen. Thus it can be seen that 1) the theme in the novel